Comparative Analysis of Groundwater Quality Based on Chemical Parameters Around Final Disposal Sites Using Open Dumping and Sanitary Landfill Methods - Amadia, Shiesil Rizqia; Humairo, Mika Vernicia (citeus, 2025)
The main environmental issue at landfill sites is the seepage of leachate into the ground, which contaminates surrounding aquifers. Communities residing within one kilometer of landfill sites are at high risk of environmental pollution. This study aimed to analyze differences in groundwater quality around landfills applying open dumping and sanitary landfill methods, and to compare groundwater quality at safe and unsafe distances from these sites. The research was conducted around the Cipayung landfill in Depok (open dumping) and the Talangagung landfill in Kepanjen (sanitary landfill). The study adopted an analytical observational approach using a cross-sectional design. The independent variables included landfill management method and distance, whereas the dependent variables encompassed chemical parameters of ammonia, iron, and manganese. Sampling was carried out purposively in areas located up to 1.5 km from the landfill, where groundwater wells were still used as clean water sources. A Mann–Whitney U test was applied to analyze the collected data. There were no substantial variations in groundwater quality with respect to distance from the landfill in terms of ammonia, iron, and manganese levels. However, a significant difference (p < 0.05) was identified in overall chemical parameters between landfills applying open dumping and sanitary landfill methods. Conclusion: Several groundwater points around the open dumping landfill showed ammonia and manganese levels exceeding quality standards, while all parameters around the sanitary landfill site remained below the standard limits.